2012
DOI: 10.1371/journal.pone.0039835
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Porcine In Vitro Model of the Blood-Cerebrospinal Fluid Barrier with Strong Barrier Function

Abstract: Epithelial cells of the plexus choroideus form the structural basis of the blood-cerebrospinal fluid barrier (BCSFB). In vitro models of the BCSFB presenting characteristics of a functional barrier are of significant scientific interest as tools for examination of BCSFB function. Due to a lack of suitable cell lines as in vitro models, primary porcine plexus epithelial cells were subjected to a series of selective cultivation steps until a stable continuous subcultivatable epithelial cell line (PCP-R) was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Of note, we also established a novel porcine choroid plexus epithelial cell line (PCP-R), which displays important features of a functional BCSFB in vitro model, i.e. the formation of a strong barrier function as demonstrated by a high TEER and a low permeability for macromolecules [33]. In preliminary experiments, this cell line seems also to be suitable for the establishment of an inverted cell culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we also established a novel porcine choroid plexus epithelial cell line (PCP-R), which displays important features of a functional BCSFB in vitro model, i.e. the formation of a strong barrier function as demonstrated by a high TEER and a low permeability for macromolecules [33]. In preliminary experiments, this cell line seems also to be suitable for the establishment of an inverted cell culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Choroid plexus epithelial cell lines that display the characteristic properties of the BCSFB have been described (140,141); however, the majority of in vitro microbial invasion studies have been performed using monocultures of brain microvascular endothelial cells.…”
Section: In Vivo and In Vitro Models Of Cns Invasionmentioning
confidence: 99%
“…Using a VO device Stazielle and Ghersi-Egea ( 1999 ) recorded 187 Ω cm 2 in primary rat CPE, while Baehr et al ( 2006 ) reported 100-150 Ω cm 2 in pig choroid plexus, and commented this would be equivalent to ~600 Ω cm 2 in an impedance system. Using a VO system with a stable continuous subcultivatable porcine CPE cell line, Schroten et al ( 2012 ) reported TEER >600 Ω cm 2 . In general the values up to ~600 Ω cm 2 fi t better with evidence for leakier tight junctions in CPE than BBB (Bouldin and Krigman 1975 ), but it is clear that more "side-by-side" comparisons of VO and IS systems using a particular in vitro model would be helpful to clarify the situation.…”
Section: Impedance Spectroscopy Systemsmentioning
confidence: 99%
“…6.1.4.3 ), some models are tight enough for demonstration of CSF secretion, and the models have been used for a variety of studies of transport, metabolism and leukocyte traffi c (Redzic 2013 ;Strazielle and GhersiEgea 2013 ;Monot and Zheng 2013 ). A stable continuous sub-cultivatable porcine cell line (PCP-R) (Schroten et al 2012 ) and some immortalized cell lines (human Z310, Monot and Zheng 2013 ; rat TR-CSFB3, Terasaki and Hosoya 2001 ) have been introduced. The models have generally not been used for drug permeability screening.…”
Section: Choroid Plexus Epithelial (Cpe) Cellsmentioning
confidence: 99%